A comparative analysis of regional permeability of the material for the fixation of andsystem (Эндодонтия Today)
The dentist on therapeutic reception is always a matter of choice, of choosing a particular method or material in a particular clinical situation. This relates to the question of the application of endodontic systems: for or against? Unfortunately, it is uncertain at what minimum amount you need to use pins. It is also necessary to remember about the anatomical features of the teeth and roots that need to be considered when selecting endodontic systems. And, of course, fixing the posts on syler, we must achieve coronal and root of Hermeticism. In this paper, we conducted a comparative analysis of microbacteria of sileru used for fixing different in its structure posts: fiberglass and anchor pin. The teeth were divided into 2 groups. In the first group studied the permeability of glass ionomer material Fuji 9, on which were fixed anchor pins in the second group used the fiberglass pins for the cementation which used self-adhesive composite cement Relyx U200. When comparing adhesive fixation strength of different materials noted that the cement Relyx U200 provides the highest rate.